The association between dietary antioxidant quality score and uric acid related mortality in patients with chronic kidney disease - Shi, Shuai; Fang, Qiang (Frontiers in Nutrition, 2024)
Aim: Antioxidants diet is beneficial for the prognosis of chronic kidney disease (CKD).However, the relationship between the Dietary Antioxidant Quality Score (DAQS), a measure of overall quality on antioxidant diet, and hyperuricemia related mortality is unclear. This study aimed to investigate the relationship between the DAQS and hyperuricemia mortality in CKD patients.: In this cohort study, data were collected in the National Health and Nutrition Examination Survey (NHANES) from 2009 to 2018. The DAQS was calculated based on the six dietary antioxidants. Mortality status were determined by NHANES-linked National Death Index public access files through December 31, 2019. Weighted Cox proportional hazard models were used to investigate the association between the DAQS and hyperuricemia related mortality.Results: A total of 3684 participants were included. During the median follow-up of 63.83 months, 820 deaths were recorded. The results showed that higher dietary antioxidants intake associated with lower hyperuricemia related mortality risk among CKD patients (HR=1.28, 95%CI: 1.07 to 1.54). In subgroup analyses, the association of antioxidants intake and hyperuricemia related mortality risk remained exist in groups of aged ≥65 years (HR=1.23, 95%CI: 1.01 to 1.52), with hypertension (HR=1.26, 95%CI: 1.02 to 1.55), with dyslipidemia (HR=1.30, 95%CI: 1.07 to 1.58), with CVD (HR=1.31, 95%CI: 1.03 to 1.67), and diabetes (HR=1.62, 95%CI: 1.24 to 2.12).Higher antioxidants intake associated with lower odds of hyperuricemia related mortality in CKD patients. Future interventional studies are needed to elucidate the beneficial effect of antioxidants diets.